The Influence of Financial Literacy and Access to Financing on the Profitability of MSMEs in Gorontalo: An Empirical Analysis - Kamaru, Izmiranty Putri; Hasri, Nurhalisa; Hanapi, Nurisrawati; Budiawan, Shella (Amsir Accounting & Finance Journal, 2025)
This study aims to analyze the influence of financial literacy and access to financing, primarily through People's Business Credit, on the profitability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In the context of the significant development of MSMEs in various regions, good financial literacy is expected to increase financial inclusion and, in turn, support business growth. The method used in this study was a survey with a questionnaire distributed to 100 MSME actors in Bandar Lampung and Gorontalo. Data analysis used linear regression techniques to identify the relationship between variables. The study results indicate that high financial literacy and reasonable access to financing positively increase MSME's profitability. These findings emphasize the importance of increasing financial literacy and access to funding for MSMEs to encourage local economic growth. Policy recommendations are aimed at the government and financial institutions to improve financial education programs and facilitate access to financing for MSMEs.